High Frequency Non-Invasive Stimulation Over the Spine: Effects on Mood and Mechanical Pain Tolerance in Normal Subjects - A. D. Towell; D. Williams; S. G. Boyd (Behavioural Neurology)
We investigated the effects of non-invasive high frequency (625Hz) stimulation over the spine on mechanical pain tolerance and subjective mood. Sixty healthy subjects were divided equally into three groups receiving either high intensity (250 V), low intensity (3–4 V) or sham electrical stimulation directly over the spinal cord for 30 minutes. Following high intensity stimulation, subjects felt significantly more elated, leisurely and less tense and, contrary to reports on patients with clinical pain, had lower mechanical pain tolerances. There were no correlations between changes in mood and changes in mechanical pain tolerances. These findings contrasted with the lack of any significant differences in mood or mechanical pain tolerances in a second study where 20 subjects received either high intensity or sham stimulation across the left shoulder joint. The results indicate that decreases in mechanical pain tolerance are independent of changes in mood following non-invasive high frequency, high intensity cutaneous stimulation but that both effects are dependent on that stimulation being applied over the spine.